Estudio de las relaciones entre parámetros estructurales de sistemas porosos desordenados y la difusividad efectiva mediante Monte Carlo Cinético (2011)
ABSTRACT: The effect of porosity and pore size on transport properties of hydrogen in a disordered porous medium is studied by kinetic Monte Carlo. The randomness of the pores in the medium, inscribed inside a simple cubic lattice, was corroborated by calculating the percolation threshold from the order parameter. In regard to mass transport, results suggest that pore size varied between 1 and 5 nm only affects the effective diffusion if porosity values are close to the percolation threshold. Moreover, such diffusivity is mostly independent of H2 molecules concentration. Simulation allowed to characterize the anomalous diffusional behavior as a function of porosity, and it is consequent to the previously reported results for two-dimensional lattices.